Effect of medium composition on the growth and asparaginase production of Vibrio succinogenes. - Albanese, E (1978)
Asparaginase synthesis by Vibrio succinogenes is induced by ammonium ions. Synthesis occurs throughout exponential phase, and in early stationary phase asparaginase accounts for about 5% of the total soluble protein. The organism grows best when fumarate is provided as the terminal electron acceptor of the formate-oxidizing cytochrome system. Yeast extract or enzyme-hydrolyzed proteins are effective nutrient sources. In an ammonium formate-sodium fumarate medium, where maximum growth and asparaginase synthesis occurs, the total enzyme yield (international units per liter of culture) is about one-tenth that obtainable with a good asparaginase-producing strain of Escherichia coli. The energetic inefficiency of V. succinogenes appears to cause a low yield of cells and therefore low total enzyme yield. However, the levels of asparaginase accumulated within cells raise questions about the organism's protein synthesizing system.